Key stage 2 attainment, Academic year 2022/23 - ONS (2023)
This publication provides revised attainment and progress statistics for key stage 2 national curriculum assessments in England. It is an update to the provisional statistics published on 12 September 2023 and extends the Key stage 2: National headlines statistics published on 11 July 2023. Progress measures of pupils between key stage 1 and key stage 2 are included. These statistics cover attainment in assessments taken by pupils at the end of year 6, when most are age 11. It includes results for pupils in schools in England: at national level, broken down by the following pupil characteristics: gender, disadvantage, free school meal eligibility, ethnicity, special educational need status, first language and month of birth; at national level, broken down by the following school characteristics: school type, school phase, cohort size and school religious character; at regional and local authority level, broken down by pupil characteristics: gender, disadvantage, free school meal eligibility, ethnicity, special educational need status and first language; at local authority district, school location and pupil residency broken down by disadvantage, free school meal eligibility and school type. Some of these breakdowns are not discussed in the text but can be accessed via the table tool or by downloading the data files. All gaps and percentage point differences are calculated from unrounded figures.
KerkoCite.ItemAlsoKnownAs: 2129771:9MF9TFDU 2486141:JV6ENTGV